Evaluation of Productivity and Egg Quality in Japanese Quails Reared Under Different LED Colors and Rearing Systems - Paitoon Kaewhom; Kraiyot Saelim; Patcharawadee Poolsamran; Chanathip Thammakarn; Chanporn Chaosap; Rasheed Olayiwola Sulaimon; Panneepa Sivapirunthep; Kanokrat Srikijkasemwat (Veterinary Sciences, 2026)
< 0.05). In conclusion, red LED light optimizes long-term profitability, whereas the floor system offers distinct advantages during the onset of lay.
Keywords: Animal Nutrition and Physiology; Livestock and Poultry Management; Antioxidant Activity and Oxidative Stress